2020
DOI: 10.1002/ana.25670
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Glymphatic Pathway and Putative Meningeal Lymphatic Vessels in the Aging Human

Abstract: Objective Aging is a major risk factor for numerous neurological disorders, and the mechanisms underlying brain aging remain elusive. Recent animal studies demonstrated a tight relationship between impairment of the glymphatic pathway, meningeal lymphatic vessels, and aging. However, the relationship in the human brain remains uncertain. Methods In this observational cohort study, patients underwent magnetic resonance imaging before and at multiple time points after intrathecal administration of a contrast age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
185
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(225 citation statements)
references
References 28 publications
16
185
0
Order By: Relevance
“…Recent animal and human studies have shown that intrathecal gadolinium injections lead to peri-sinus contrast enhancement in dural lymphatics visible on MRI at 50–200 min after intrathecal gadolinium injection; this finding supports the assertion that there is a link between the glymphatic system and MR-visible dural lymphatics [ 10 , 31 , 32 ]. Therefore, the direct assessment of the dural lymphatics via MRI may offer an in vivo evaluation of the glymphatic system and further study is required to explore MRI-visible dural lymphatics and their relationships with the glymphatic system.…”
Section: Discussionsupporting
confidence: 54%
“…Recent animal and human studies have shown that intrathecal gadolinium injections lead to peri-sinus contrast enhancement in dural lymphatics visible on MRI at 50–200 min after intrathecal gadolinium injection; this finding supports the assertion that there is a link between the glymphatic system and MR-visible dural lymphatics [ 10 , 31 , 32 ]. Therefore, the direct assessment of the dural lymphatics via MRI may offer an in vivo evaluation of the glymphatic system and further study is required to explore MRI-visible dural lymphatics and their relationships with the glymphatic system.…”
Section: Discussionsupporting
confidence: 54%
“…Measurements of signals at locations including the ventricles and brain parenchyma, predefined as the “glymphatic pathway” showed that the delayed clearance of the “glymphatic pathway” was related to aging. The study also examined heavily T2-weighted fluid-attenuated inversion recovery images to visualize putative meningeal lymphatic vessels; the delayed visualization of meningeal lymphatics compared to that of the “glymphatic pathway” indicated that meningeal lymphatics are downstream of the “glymphatic pathway” ( 28 ). Practically, the intrathecal injection of GBCAs has not been approved by U.S. Food and Drug Administration (FDA), making its clinical application impossible.…”
Section: Imaging Evaluation Of the Glymphatic System/neurofluid Dynammentioning
confidence: 99%
“…MRI has provided the evidence of presence of meningeal lymphatic vessels in human and non-human primates for CNS waste clearance [66]. A very recent study on humans utilizing MRI provided a clinical methodology to simultaneously visualize the glymphatic system clearance, deep cervical lymph nodes, and putative meningeal lymphatic vessels [30]-this MRI study also reported decreased glymphatic system and meningeal lymphatic CSF tracer clearance with increased age [30].…”
Section: Magnetic Resonance Imaging (Mri) Detection and Modelingmentioning
confidence: 95%
“…Normal physiology (such as blood pressure [21], sleep [14], anesthesia [22], body posture [23], and aging [19,21,[24][25][26][27][28][29][30]) affects the glymphatic system. It was demonstrated that a 10 bpm decrease in heart rate (bradycardia) reduces waste clearance and results in a nearly 20% additional accumulation of beta-amyloid in the brain parenchyma, whereas a 30 bpm increase in heart rate (tachycardia) showed a nearly 30% reduction in beta-amyloid levels in the brain parenchyma [21].…”
Section: Introductionmentioning
confidence: 99%